EMOTIONAL INTELLIGENCE IN LEADERSHIP: A CROSS-CULTURAL ANALYSIS OF EMPLOYEE ENGAGEMENT AND RETENTION - Raghav, S. Venkat; SM, Padmavathi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study explores the critical role of emotional intelligence (EI) in leadership across different cultural contexts and its impact on employee engagement and retention. By analyzing diverse leadership approaches and employee responses within multinational organizations, the paper examines how leaders' emotional intelligence enhances team cohesion, boosts motivation, and reduces turnover rates. Through a mixed-methods approach incorporating quantitative data and qualitative case studies, this research identifies key emotional intelligence competencies that foster higher levels of employee satisfaction and long-term commitment. The findings underscore the importance of culturally adaptive leadership that leverages emotional intelligence as a strategic asset for improving organizational performance and sustainability. Recommendations for training programs aimed at developing EI-driven leadership strategies are provided, emphasizing the need for customized approaches that account for cultural nuances.